2011
DOI: 10.1071/mu10033
|View full text |Cite
|
Sign up to set email alerts
|

Observed and predicted effects of climate on Australian seabirds

Abstract: Although there is growing evidence of climate warming, for many regions the broader effects of climate variation on marine top predators remains unknown owing to the difficulty in obtaining, for synthesis, long-term and shortterm datasets on multiple species. In the Australian region, climatic and oceanographic variability and change have been shown to affect marine species, often with profound consequences. Many seabirds are apex predators for which changes in climatic and oceanic dynamics have driven range m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 117 publications
(11 reference statements)
1
65
0
Order By: Relevance
“…Over the last two decades, breeding participation in three species, Lesser Noddy Anous tenuirostris, Brown Noddy A. stolidus and Sooty Tern Onychoprion fuscata, was lower in years of later breeding, though the resident Lesser Noddies appeared to be more resilient than the two migratory species . There is some evidence that ENSO influences the timing of breeding in Western Australian Laridae, with potentially new (but as yet unknown) complicating factors appearing in more recent years, resulting in reduced reproductive performance in both ENSO and non-ENSO years (Surman and Nicholson 2009b;Chambers et al 2011).…”
Section: Seabird Breeding Phenologymentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last two decades, breeding participation in three species, Lesser Noddy Anous tenuirostris, Brown Noddy A. stolidus and Sooty Tern Onychoprion fuscata, was lower in years of later breeding, though the resident Lesser Noddies appeared to be more resilient than the two migratory species . There is some evidence that ENSO influences the timing of breeding in Western Australian Laridae, with potentially new (but as yet unknown) complicating factors appearing in more recent years, resulting in reduced reproductive performance in both ENSO and non-ENSO years (Surman and Nicholson 2009b;Chambers et al 2011).…”
Section: Seabird Breeding Phenologymentioning
confidence: 99%
“…In light of the conservation status of many of the world's seabirds, that a high proportion of the most threatened species are in the southern hemisphere, and that many seabirds are influenced by climatic changes in their marine and terrestrial environments (reviewed by Chambers et al 2011Chambers et al , 2013a, this paper aims to:…”
Section: Introductionmentioning
confidence: 99%
“…Nevoux et al 2007;Rolland et al 2010). Chambers et al (2011) pointed out further potential impacts of climate change, including effects of rises in sea level and storms, ocean acidification, changing wind patterns, increased land temperature and extreme precipitation events.…”
Section: South American Large Marine Ecosystems and Climatementioning
confidence: 99%
“…Several recent reviews suggested that global warming has a profound bottom-up impact upon marine top-predators (e.g. Grémillet & Boulinier 2009;Chambers et al 2011). Climate change also increasingly affects seabirds.…”
Section: Introductionmentioning
confidence: 99%
“…But for some scientific issues, such as the study of trans-hemisphere migration, for example, events in one hemisphere affect life-history stages in the other hemisphere. This means that when considering the potential effects of climate change (Chambers et al 2011) or disease ecology (Klaassen et al 2011), the two hemispheres cannot be considered separately.…”
mentioning
confidence: 99%